Love Letters to the Future: REP, Radical America, and New Left History. - McMillian, John (Radical History Review)
Investigates two intellectual projects launched by the New Left Students for a Democratic Society. Features of the Radical Education Project; Details on the journal 'Radical America' of the organization; Reasons for launching the intellectual projects.